A lab-scale prototype development of Lignin-Formaldehyde (LF) resin: A bio-renewable adhesive for wood panel industries - Arsalan Yousafzai; Tufail Rahman; Sana Ahmad; Muzaffar Iqbal; Ambar Farooq; Majid Hussain (PLoS ONE, 2026)
This study evaluated laboratory-prepared wood adhesives synthesized from alkaline lignins isolated from three locally available biomasses: chir pine needles (CP), eucalyptus sawdust (ESD), and sugarcane bagasse (SB). After alkaline extraction, each lignin was reacted with formaldehyde under alkaline conditions to synthesize resol-type lignin-formaldehyde resins under a complete phenol-replacement system. The Lignins differed in molecular weight, extraction yield, and hydroxyl distribution. Quantitative 31 P NMR showed total OH + COOH contents of 3.70 mmol g -1 for CP, 4.60 mmol g -1 for ESD, and 4.83 mmol g -1 for SB. Thermogravimetric analysis indicated comparable thermal stability among the lignins, with char yields of 19.22–24.23% at 1000°C. The lignin formaldehyde (LF) resin showed alkaline pH, workable solid content, 3–4shear-thinning viscosity, and gel times suitable for laboratory hot pressing. Differential scanning calorimetry confirmed curing in the hot-pressing temperature range, with CP resin showing the highest glass transition temperature. In lap-shear testing, the laboratory phenol formaldehyde (PF) control showed the highest dry and wet strengths, while CP performed best among the LF resins, followed by ESD and SB. The results show that adhesive performance was not governed by total hydroxyl content alone. Instead, feedstock-dependent lignin structure, hydroxyl distribution, molecular size, and cured-network development jointly influenced bond strength and moisture resistance. The study supports the laboratory-scale potential of Pakistani biomass residues for lower-phenol wood adhesive development, while further work is needed on residual carbohydrates, panel formaldehyde emissions, commercial PF benchmarking, and scale-up feasibility.